Pentingnya Kepercayaan Diri dan Motivasi Sosial dalam Keaktifan Mengikuti Proses Kegiatan Belajar SD Muhammadiyah PK Baturan - Rafida Azzahra Prasetyo Putri; Rifayani Hastuti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Every human personality, confidence is an important indicator to produce success in relation to the activities that he does. However, there are things that cannot be denied that the level of confidence possessed by each individual is different, and al is influenced by other factors besides the process of maturity tself. A student's confidence in his activities when participating in teaching and learning activities is not only influenced by social motivation but also influenced by the ability in the knowledge he has. In the discussion in this research that is to help how to grow self-confidence for students in their activities when following the process of teaching and learning activities, how the social motivation of students of SD Muhammadiyah PK Baturan. How is the influence between self-confidence on motivation in activeness to follow the process of teaching and learning activities at SD Muhammadiyah PK Baturan. The population in this study was to take samples at the first semester level I students of the SD Muhammadiyah PK Baturan Public Health Study Program in 2023/2024 with a total of 25 students, this study was conducted using descriptive qualitative methods. Because this method is considered able to uncover, explore and analyze empirical phenomena that occur at the present time by describing or describing in accordance with the facts that occur from the results of the study.